HUBUNGAN PEMBERIAN NUTRISI DENGAN KEJADIAN REGURGITASI DI PMB BIDAN L KOTA BANDUNG - Gina Rismaliani; Maya Indriati; Naili Rahmawati (Universitas Batam, 2023)
Regurgitation or spitting up is the backflow of stomach contents into esophagus, out through mouth and is not accompanied by contractions of the abdominal muscles. This research will be conducted using primary data and secondary data. This study entitled